A Bridge No Longer Too Far: A Case Study of One School's Exploration of the Promise and Possibilities of Mind, Brain, and Education Science for the Future of Education. Issue 4 (8th March 2018) - Kelleher, Ian; Whitman, Glenn
ABSTRACT: Mind, brain, and education (MBE) science research continues to produce valuable results about brain development and the learning process—research that can and should inform education reform. Given the link between teacher efficacy and student learning outcomes, MBE is a discipline with considerable promise to help close gaps in school and teacher quality and student achievement. Yet, in our experience working with thousands of K‐12 teachers, very few have been trained to adapt their instructional strategies in ways that are informed by MBE research. Research on what helps and hinders learning exists, but, as yet, effective and efficient ways to translate it into classroom practice are rare. This article presents a case study of how one school is bridging the gap between MBE research and its integration into the classroom, a gap that was once deemed "a bridge too far" to cross. It also suggests a series of steps that form a possible translational pathway for teachers, school leaders, and policymakers.